Telegram (copy) - Citrine, Walter, 1887-1983
012a-0122-001 (PROPOSED TELEGRAM). 1.4.38. To [shorthand] UGT [shorthand] BRITISH LABOUR MOVEMENT GREATLY CONCERNED AT SERIOUS DEVELOPMENTS IN SPAIN. LABOUR PARTY AGAIN RAISING QUESTION IN HOUSE COMMONS MONDAY STOP SPECIAL SERIES DEMONSTRATIONS ORGANISED THROUGHOUT COUNTRY STOP WILL DO EVERYTHING PRACTICABLE TO EXERT PRESSURE ON GOVERNMENT TO REMOVE ARMS EMBARGO CITRINE. Sent at own risk. We shall be notified if it does not arrive. WJB/AC/428.1.4. 292/946/12a/122